How Knowledge Shapes Public Perception of the Covid-19 Vaccine - Koko Wahyu Tarnoto; Ros Endah Happy Patriyani; Mumtazah, Anisah Azzah; Astuti, Athanasia Budi (Poltekkes Kemenkes Surakarta, 2023)
Background: In 2021, Covid-19 cases in Indonesia decreased by 82% following the implementation of a mass vaccination program. The Covid-19 vaccine, which uses a weakened virus, helps prevent transmission, reduce morbidity and mortality, and increase immunity to the virus. This study analyzes the relationship between the level of knowledge and public perception of the Covid-19 vaccine. Methods: This quantitative study employed a cross-sectional design. A purposive sampling technique was used, resulting in 154 respondents. Data were collected via an online questionnaire, and analyzed using the Spearman Rank correlation test. Results: The Spearman Rank test revealed a significant relationship between the level of knowledge and public perception of the Covid-19 vaccine, with a p-value of 0.025 (p < 0.05). Conclusion: Higher levels of public knowledge about Covid-19 are associated with more positive perceptions of the vaccine. Public education through reliable sources is essential to enhance understanding and encourage effective Covid-19 prevention practices.